KARAKTERISTIK WIRAUSAHA TERHADAP KEBERLANJUTAN INDUSTRI KULINER TRADISIONAL - Abubakar, Herminawaty; Palisuri, Palipada (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
Household industries and small industries in Rappang Urban Village generally move in the field of traditional culinary, where traditional culinary is a typical culinary District Sidrap which has been known for a long time. The management of traditional culinary industry in Rappang Urban Village is still very traditional, touch of technology and modern management is still far from the reach of businessmen thinking that move in this culinary field. This study aims to analyze the influence of entrepreneurial characteristics on the sustainability of traditional culinary business. This paper uses a quantitative approach. Data obtained through questionnaires and interviews. By using random sampling method and convenience random sampling. Respondents in this research are traditional culinary industry entrepreneurs as much as 54 entrepreneurs and analytical methods used to analyze the influence between variables in research by using statistical analysis. The findings in this study, the characteristics of entrepreneurship have a positive and significant impact on the sustainability of traditional culinary business.